2011
DOI: 10.3109/0284186x.2011.572913
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome with bevacizumab in patients with recurrent high-grade glioma treated outside clinical trials

Abstract: Our data reveal valuable palliation with preservation of KPS and an option for steroid withdrawal in patients treated with BEV, supporting the role of this therapy in late-stage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 14 publications
3
22
0
Order By: Relevance
“…Numerous phase II studies have shown modest survival benefits with bevacizumab either as a monotherapy or in combination with irinotecan (Chinot et al 2011;Jakobsen et al 2011;Lai et al 2011;Prados et al 2011;Reardon et al 2011). Consistent to all trials examining bevacizumab efficacy is the reduction of steroids for patients and valuable palliation with preservation of key performance status (KPS), supporting a role for bevacizumab as a therapy in late stage disease (Hofer et al 2011). …”
Section: Targeting Angiogenesismentioning
confidence: 97%
“…Numerous phase II studies have shown modest survival benefits with bevacizumab either as a monotherapy or in combination with irinotecan (Chinot et al 2011;Jakobsen et al 2011;Lai et al 2011;Prados et al 2011;Reardon et al 2011). Consistent to all trials examining bevacizumab efficacy is the reduction of steroids for patients and valuable palliation with preservation of key performance status (KPS), supporting a role for bevacizumab as a therapy in late stage disease (Hofer et al 2011). …”
Section: Targeting Angiogenesismentioning
confidence: 97%
“…Treatment for recurrent GBM mainly comprises chemotherapy, which presents its own toxic side effects [7,11,12]. Repeated irradiation has been linked to higher complication rates [4,22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Reoperation and retreatment with radiotherapy have been associated with increased complication and morbidity rates [8,9,10]. Treatment for recurrent GBM mainly comprises chemotherapy, which presents its own toxic side effects [7,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies evaluating the efficacy of BEV monotherapy for patients with recurrent GBM have demonstrated objective RR (PR plus CR), overall survival, PFS and PFS-6 rates of 28.2-43%, 7.2-12 months, 1.0-4.2 months and 20.9-42.6%, respectively, as calculated from statistical treatment of the data (25)(26)(27)(29)(30)(31)(32)(33). Furthermore, BEV plus chemotherapy combination therapy increased RR and PFS (25,27), and additional studies of BEV in combination with cytotoxic agents including carboplatin, erlotinib, etoposide, fotemustine, CPT-11 and dose-intense daily TMZ for patients with recurrent GBM also demonstrated RR, OS, PFS and PFS-6 rates of 20-67.6%, 4.3-11.5 months, 2.5-7.6 months and 25-63.7%, respectively (Table I) (17).…”
Section: Efficacy Of Bevacizumab Treatment For Patients With Recurrenmentioning
confidence: 99%